INVESTIGATION OF THE DEPENDENCE OF THE NUMBER OF MOLECULAR JUMPS ON THE DENSITY DURING THE PROCESS OF VIBRATION RELAXATION IN LIQUIDS (Scientific journal of the Fergana State University, 2024)
In its structure, the liquid state of a substance occupies a state between a solid (crystalline) body and a gas. Due to the thermal movement of molecules in liquids, the order of the structure is continuously destroyed and restored, which indicates the closeness of the structure of liquids to the structure of gases. The peculiarity of the structure of the liquid leads to difficulties in the theoretical description of this state of matter. For this reason, model diagrams are widely used in fluid theory. Theories of vibrational relaxation in liquids are based on two different mechanisms. 1.Mechanism of isolated double collisions. 2. Mechanism of interaction with collective vibrations.